The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1002/lsm.10034
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort pulse laser ossicular ablation and stapedotomy in cadaveric bone*†

Abstract: Ultrashort pulse lasers may provide a useful clinical tool for otologic and skull base surgery, where precise hard tissue ablation is required adjacent to critical structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 24 publications
(25 reference statements)
8
22
2
2
Order By: Relevance
“…The same authors reported that at 2.0 J/cm 2 , they were removing 1.26 mm/pulse. Initially, as a very crude approximation, since we have been able to cut 200 mm of bone that is not fully calcified with 225 pulses, this gives an approximate removal of material of 1 mm per pulse, which is in agreement with Neev et al [23] as well as other studies [24,25].…”
Section: Ablation Threshold and Ablation Ratesupporting
confidence: 76%
“…The same authors reported that at 2.0 J/cm 2 , they were removing 1.26 mm/pulse. Initially, as a very crude approximation, since we have been able to cut 200 mm of bone that is not fully calcified with 225 pulses, this gives an approximate removal of material of 1 mm per pulse, which is in agreement with Neev et al [23] as well as other studies [24,25].…”
Section: Ablation Threshold and Ablation Ratesupporting
confidence: 76%
“…31 In ultrafast ablation, thermal damage is usually limited because the dominate ablation mechanism is not thermal based and the total deposited energy is low. 21 In our results, including those reported earlier using similar parameters, 24 very little thermal damage was observed on the side of the crater.…”
Section: Summary and Discussionsupporting
confidence: 84%
“…19,20 Benefiting from the plasma-induced ablation mechanism, ultrafast pulsed lasers emerge as a promising candidate for hard-tissue ablation because they offer high resolution with minimal thermal-related damage in the collateral tissues. [21][22][23][24] On the other hand, tight focusing and small volume of tissue removal are typical in ultrafast laser ablation, which make it difficult to produce large structures needed in clinical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Cortical bone was irradiated at 775nm with pulses of decreasing energy until no further material removal was observed. The calculated ablation threshold for bone at 775nm is 0.9J«cm-2 and this is consistent with [2]. By doubling the laser frequency, we have found the bone ablation threshold at 387nm to be 0.3J«cm-2…”
Section: Resultssupporting
confidence: 76%